Enhanced Optical Properties of Germanate and Tellurite Glasses Containing Metal or Semiconductor Nanoparticles - Cid Bartolomeu de Araujo; Diego Silvério da Silva; Thiago Alexandre Alves de Assumpção; Luciana Reyes Pires Kassab; Davinson Mariano da Silva (The Scientific World Journal)
Germanium- and tellurium-based glasses have been largely studied due to their recognized potential for photonics. In this paper, we review our recent studies that include the investigation of the Stokes and anti-Stokes photoluminescence (PL) in different glass systems containing metallic and semiconductor nanoparticles (NPs). In the case of the samples with metallic NPs, the enhanced PL was attributed to the increased local field on the rare-earth ions located in the proximity of the NPs and/or the energy transfer from the metallic NPs to the rare-earth ions. For the glasses containing silicon NPs, the PL enhancement was mainly due to the energy transfer from the NPs to the Er3+ ions. The nonlinear (NL) optical properties of PbO-GeO2 films containing gold NPs were also investigated. The experiments in the pico- and subpicosecond regimes revealed enhanced values of the NL refractive indices and large NL absorption coefficients in comparison with the films without gold NPs. The reported experiments demonstrate that germanate and tellurite glasses, having appropriate rare-earth ions doping and NPs concentration, are strong candidates for PL-based devices, all-optical switches, and optical limiting.